Digital Literacy Management to Increase Students' Reading Interest and Soft Skills: Multisite Study at SMKN 1 Driyorejo and SMKN 1 Cerme Gresik - Hudha, Much; W, Dewie Tri Wijayati; Khamidi, Amrozi; Nursalim, Mochamad (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe and analyze the management of digital literacy programs implemented at SMKN 1 Driyorejo and SMKN 1 Cerme as a strategy to increase students' reading interest and soft skills. This study uses a qualitative approach with a multi-site study design, through observation techniques, in-depth interviews, and documentation. The results of the study show that the digital literacy program in both schools is designed based on contextual needs and has been implemented through various strategies such as project-based learning, the use of digital platforms, and the development of multimedia teaching content. The main difference lies in the orientation approach: SMKN 1 Driyorejo emphasizes active student participation and digital collaboration, while SMKN 1 Cerme is more structured and oriented towards the development of standardized digital learning content. Evaluation is carried out formative and summative by utilizing digital instruments and students' reflections. The cross-case results show that flexibility, collaboration, and the use of technology are key factors in the success of empowerment-based digital literacy programs in vocational schools.